Potential biomarkers: Identifying powerful tumor specific T cells in adoptive cellular therapy - Ge, Wu; Dong, Yuqian; Deng, Yao; Chen, Lujuan; Chen, Juan; Liu, Muqi; Wu, Jianmin; Wang, Wei; Ma, Xiaoqian (Frontiers in Immunology, 2022)
Tumor-specific T cells (TSTs) are essential components for the success of personalized tumor-infiltrating lymphocyte (TIL)-based adoptive cellular therapy (ACT). Therefore, the selection of a common biomarker for screening TSTs in different tumor types, followed by ex vivo expansion to clinical number levels can generate the greatest therapeutic effect. However, studies on shared biomarkers for TSTs have not been realized yet. The present review summarizes the similarities and differences of a number of biomarkers for TSTs in several tumor types studied in the last 5 years, and the advantages of combining biomarkers. In addition, the review discusses the possible shortcomings of current biomarkers and highlights strategies to identify TSTs accurately using intercellular interactions. Finally, the development of TSTs in personalized TIL-based ACT for broader clinical applications is explored.